দীপালিকা, দ্বিতীয় শ্রেণি - (:unkn) unknown (Tripura Board of Secondary Education, 2016)
This is a Bengali text book for second standard (Class II) of Tripura board of secondary education.
Dipalika, Class-II
Keywords: Bengali; Bengali; Bengali; Bengali